Gamma radiolytic degradation of naphthalene in aqueous solution. (June 2016) - Chu, Libing; Yu, Shaoqing; Wang, Jianlong
Abstract: The decomposition of naphthalene in aqueous solution was studied using gamma irradiation combined with both H2 O2 and TiO2 nanoparticles. Gamma irradiation led to a complete degradation of naphthalene and a partial mineralization. With initial concentration of 5–32 mg/L, more than 98% of naphthalene was removed and TOC reduction reached 28–31% at an absorbed dose of 3.0 kGy. The degradation of naphthalene was faster at neutral pH and the initial degradation rate increased with increasing the initial concentration of naphthalene. Addition of H2 O2 and TiO2 nanoparticles all enhanced the degradation and mineralization of naphthalene. TOC removal efficiency increased from 28% (irradiation alone) to 35% with addition of H2 O2 (40 mg/L), and to 48% with addition of TiO2 (0.8 g/L). The degradation of naphthalene in aqueous solution by gamma irradiation was mainly through the oxidation by· OH radicals. The intermediate naphthol and carboxylic acids such as formic acid and oxalic acid were identified by LC–MS and IC. Highlights: Gamma irradiation led to complete removal of naphthalene and partial mineralization. Degradation rate was higher at higher initial conc., lower dose rate and neutral pH. Addition of H2 O2 and TiO2 exhibited synergetic effect on naphthalene degradation. TiO2 was favorable due to higher TOC removal and low cost in practical application.